Competition in electricity markets. (Energy market reform, 2001)
This book analyses the development of choice and competition in the Electricity Supply Industry (ESI). Drawing on a review of the international experience, it describes the main approaches that are being developed, discusses the key issues in the effective reform of electricity markets and provides an assessment of the emerging approach to reform. This book is the latest in a series of IEA publications on energy market reform.